Kwame Nkrumah. Vision and Tragedy - Rooney, David (Book collections on Project MUSE., 2007)
""The yearlong celebration of Ghana's Golden Jubilee provides a fitting context for the republication of the book Kwame Nkrumah: Vision and Tragedy. In the lead-up to the celebration and over the course of the year, the life and times of Kwame Nkrumah will receive unprecedented public attention, official and unofficial. Kwame Nkrumah's very wide name-recognition is, paradoxically, accompanied by sketchy, often oversimplified knowledge about the events and processes of his life and times. For most of those born after independence in 1957, such knowledge does not extend much beyond who Kwame Nkr